Security Mechanism for MANETs - Yasir Abdelgadir , Mohamed; Azween, Abdullah (2008)
Be short of well-defined networks boundaries, shared medium, collaborative services, and dynamic nature, all are representing some of the key characteristics that distinguish mobile ad hoc networks from the conventional ones. Besides, each node is a possible part of the essential support infrastructure, cooperate with each other to make basic communication services available. Forwarding packets or participating in routing process, either of each can directly affect the network security state. Nevertheless, ad hoc networks are suspectable to the same vulnerabilities and prone to the same types of failures as conventional networks. Even though immune-inspired approaches aren’t essentially new to the research domain, the percentage of applying immune features in solving security problems fluctuates. In this paper, security approach based on both immunity and multi-agent paradigm is presented. Distributability, second response, and self recovery, are the hallmarks of the proposed security model which put a consideration on high nodes mobility.